Extending the long‐term record of volcanic SO2 emissions with the Ozone Mapping and Profiler Suite nadir mapper. Issue 3 (10th February 2015) - Carn, S. A.; Yang, K.; Prata, A. J.; Krotkov, N. A.
Abstract Uninterrupted, global space‐based monitoring of volcanic sulfur dioxide (SO2) emissions is critical for climate modeling and aviation hazard mitigation. We report the first volcanic SO2 measurements using ultraviolet (UV) Ozone Mapping and Profiler Suite (OMPS) nadir mapper data. OMPS was launched on the Suomi National Polar‐orbiting Partnership satellite in October 2011. We demonstrate the sensitivity of OMPS SO2 measurements by quantifying SO2 emissions from the modest eruption of Paluweh volcano (Indonesia) in February 2013 and tracking the dispersion of the volcanic SO2 cloud. The OMPS SO2 retrievals are validated using Ozone Monitoring Instrument and Atmospheric Infrared Sounder measurements. The results confirm the ability of OMPS to extend the long‐term record of volcanic SO2 emissions based on UV satellite observations. We also show that the Paluweh volcanic SO2 reached the lower stratosphere, further demonstrating the impact of small tropical volcanic eruptions on stratospheric aerosol optical depth and climate.